(untitled) (WidyaAmrita: Jurnal Manajemen, Kewirausahaan dan Pariwisata, 2023)
The decision to buy a product offered by a company is very important because it affects the sustainability of achieving company goals. The purpose of this study was to determine the effect of brand image and service quality on purchasing decisions for Oppo branded smartphones at the Permaisuri Seluler Counter in Denpasar. Data will be collected by conducting interviews and distributing questionnaires. The population in this survey is all consumers of Counter Empress Cellular in Denpasar in 2020. The sample used in this survey consists of 89 respondents using the purposive sampling method. The method of data analysis in this study is multiple linear regression analysis. The results showed that purchasing decisions were influenced by brand image and service quality positively and significantly. Suggestions for improving brand